Endophyte community shifts in Rubus chingii during fruit ripening are associated with key metabolites - Xie, Yin; Dai, Di; Zeng, Huiting; Tian, Yingying; Zou, Chao; Meng, Yan; Wu, Zhaoxiang; Li, Jing (Frontiers in Plant Science, 2025)
IntroductionThe fruit of Rubus chingii Hu is a prized traditional medicine and functional food, with its quality predominantly determined by its secondary metabolites. While the metabolic dynamics during fruit ripening are documented, the role of the endophytic microbiome, a key regulator of plant physiology, remains entirely unexplored.MethodsAn integrated approach, combining 16S/ITS amplicon sequencing with spectroscopic and chromatographic analyses, were employed to investigate the correlation between the endophytic microbiome and the metabolome across four distinct ripening stages of R. chingii fruit.ResultsSignificant stage-dependent shifts in the community structure of both bacterial and fungal endophytes were revealed in this study. Notably, Spearman correlation analysis identified specific microbial taxa, including the bacterial genera Geodermatophilus and Brevundimonas, and the fungal yeasts Metschnikowia and Starmerella, that were significantly positively correlated with the accumulation of key secondary metabolites (ellagic acid, flavonoids, and phenolic acids). Concurrently, the content of these beneficial metabolites and the fruit’s antioxidant capacity decreased markedly as ripening progressed.DiscussionThis study provides the first evidence of a structured succession in the endophytic microbiome of R. chingii fruit and its close association with the dynamics of medically relevant metabolites. The findings propose that the ripening process is a tripartite interplay between host development, microbial succession, and metabolic reprogramming. The identified keystone taxa represent promising targets for future microbiome-based strategies to manipulate fruit quality, offering novel insights into the role of the microbiome in medicinal plant biology and its potential application in sustainable agriculture.